2017
DOI: 10.1515/amcs-2017-0028
|View full text |Cite
|
Sign up to set email alerts
|

Tabu Search for the RNA Partial Degradation Problem

Abstract: In recent years, a growing interest has been observed in research on RNA (ribonucleic acid), primarily due to the discovery of the role of RNA molecules in biological systems. They not only serve as templates in protein synthesis or as adapters in the translation process, but also influence and are involved in the regulation of gene expression. The RNA degradation process is now heavily studied as a potential source of such riboregulators. In this paper, we consider the so-called RNA partial degradation proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…As a continuation of the research reported in this paper, one may consider taking into account the exact RNA replication mechanism as described in [61]. Additionally, in order to reflect more accurately the RNA folding and what follows, the interactions between RNA molecules, one may consider extended secondary (taking into account both canonical and noncanonical base pairs contrary to 2D structure which considers canonical base pairs only) and tertiary interactions (formed between secondary structure elements and constituting RNA tertiary (3D) structure) within and between RNA chains [62][63][64][65][66]. However, conducting such simulations will certainly require very high computing power.…”
Section: Discussionmentioning
confidence: 99%
“…As a continuation of the research reported in this paper, one may consider taking into account the exact RNA replication mechanism as described in [61]. Additionally, in order to reflect more accurately the RNA folding and what follows, the interactions between RNA molecules, one may consider extended secondary (taking into account both canonical and noncanonical base pairs contrary to 2D structure which considers canonical base pairs only) and tertiary interactions (formed between secondary structure elements and constituting RNA tertiary (3D) structure) within and between RNA chains [62][63][64][65][66]. However, conducting such simulations will certainly require very high computing power.…”
Section: Discussionmentioning
confidence: 99%
“…For example, structural motifs can be searched for in a sequence (i.e., a primary structure), in an intramolecular interaction network (i.e., a secondary structure), or in a full-atom 3D model (i.e., a tertiary structure). Their reliable identification and analysis often bring significant insight into the understanding of biological processes (Rybarczyk et al, 2017). Structural motifs play various important biological roles, e.g., serving as binding sites in molecular complexes, indicating cleavage sites in the biogenesis of specialized molecules, blocking or initiating some cellular processes, etc.…”
Section: Introductionmentioning
confidence: 99%